Identifikasi Aspergillus fumigatus pada Sputum Pasien Suspek TB Paru - Angriani Fusvita; Firdayanti Firdayanti; Sri Yosin Vinola (Poltekkes Kemenkes Jakarta III, 2019)
Tuberculosis (TB) is a contagious infectious disease caused by the Mycobacterium tuberculosis, which can attack various organs especially the lungs. In some cases, there is a misdiagnosis between pulmonary tuberculosis and pulmonary mycosis (lung fungus). One of the species of fungus that often causing infection in the lungs is Aspergillus fumigatus.This study aims to identify Aspergillus fumigatus in sputum patients suspected of pulmonary tuberculosis patients at General Hospital in Baubau City. The types of research is descriptive with accidental sampling technique. Research was carried out by examining the BTA status of patients using the GeneXpert device and the patients sputum were isolated into Potato Dextrose Agar (PDA) medium then examined in macroscopic and microscopic (slide culture). Result of the study of 27 samples sputum patients suspected of pulmonary tuberculosis in Baubau Town Hospital obtained patients who infected Aspergillus fumigatus fungus amounted to 3 people with 2 including identified fungi with positive BTA status. Conclusion patients infected with Aspergillus fumigatus amounted to 3 people (7.4%) and 2 people (3.4%) identified fungi with positive pulmonary tuberculosis